Forecasting future trends in Dubai housing market by using Box-Jenkins autoregressive integrated moving average - Hepsen, Ali; Vatansever, Metin (EMERALD GROUP PUBLISHING LTD, 2011)
Purpose - It is important to forecast index series to identify future rises, falls, and turning points in the property market. From the point of this necessity and importance, the main purpose of this paper is to forecast the future trends in Dubai housing market. Design/methodology/approach - This paper uses the monthly time series of Reidin. com Dubai Residential Property Price Index (DRPPI) data. In order to forecast the future trends in Dubai housing market, Box-Jenkins autoregressive integrated moving average (ARIMA) forecasting method is utilized. Findings - The results of the ARIMA modeling clearly indicate that average monthly percentage increase in the Reidin. com DRPPI will be 0.23 percent during the period January 2011-December 2011. That is a 2.44 percent increase in the index for the same period. Practical implications - Reidin. com residential property price index is a crucial tool to measure Dubai's real estate market. Based on the current index values or past trend, real estate investors (i.e. developers and constructors) decide to start new projects. Attempts have also been made in the past to forecast index series to identify future rises, falls, and turning points in the property market. The results of this paper would also help government and property investors for creating more effective property management strategies in Dubai. Originality/value - There is no previous study analyzing the future trends in Dubai housing market. At this point, the paper is the first academic study that identifies this relationship.
Keywords: Dubai; Real estate; Residential property; Price index; Forecasting; Box-Jenkins; Autoregressive integrated moving average (ARIMA); Urban Studies